2019
DOI: 10.1021/acsbiomaterials.9b01681
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of the Gaseous Signaling Molecules NO, H2S, and CO in the Regulation of Stem Cells

Abstract: Stem cell technology can be used in tissue engineering and regenerative medicine to transplant stem cells of somatic, embryonic, or induced pluripotent origin, which have tremendous potential for the treatment of currently incurable diseases. Stem cells can maintain their stemness through their self-renewal capability while promoting tissue repair and regeneration through differentiation into various target tissue cells. These two major processes of stem cell biology are precisely regulated via extracellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 173 publications
0
14
0
Order By: Relevance
“…[13][14][15] As a gaseous signaling molecule, H 2 S plays an important role in human physiological and pathological processes. 16,17 H 2 S has been dened as an important endogenous neuroprotective agent that exerts protective effects through antioxidant, anti-inammatory, and anti-apoptotic mechanisms. 18,19 A signicant amount of evidence suggests that endogenous H 2 S is produced from cysteine desulfurization catalyzed by cystathionine g lyase (CSE) or cystathionine b synthase (CBS).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] As a gaseous signaling molecule, H 2 S plays an important role in human physiological and pathological processes. 16,17 H 2 S has been dened as an important endogenous neuroprotective agent that exerts protective effects through antioxidant, anti-inammatory, and anti-apoptotic mechanisms. 18,19 A signicant amount of evidence suggests that endogenous H 2 S is produced from cysteine desulfurization catalyzed by cystathionine g lyase (CSE) or cystathionine b synthase (CBS).…”
Section: Introductionmentioning
confidence: 99%
“…10,13,83,84 Given the gaseous nature of H 2 S, the straightforward inhalation of H 2 S might be a potential approach for H 2 S delivery. Like NO and CO, whose inhalable modalities have been approved for the treatment of pulmonary hypertension in newborns and launched into clinical trials for acute respiratory distress syndrome, 85 respectively, direct H 2 S inhalation indeed elicited extensive beneficial biological effects under multiple pathological conditions without producing unpleasant byproducts. [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] Notably, the landmark paper by Roth et al demonstrated that mice inhaling the desired dosage of H 2 S via modulating its partial pressure would undergo a suspended animation-like state.…”
Section: Introductionmentioning
confidence: 99%
“…Like NO and CO, whose inhalable modalities have been approved for the treatment of pulmonary hypertension in newborns and launched into clinical trials for acute respiratory distress syndrome, 85 respectively, direct H 2 S inhalation indeed elicited extensive beneficial biological effects under multiple pathological conditions without producing unpleasant byproducts. [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] Notably, the landmark paper by Roth et al demonstrated that mice inhaling the desired dosage of H 2 S via modulating its partial pressure would undergo a suspended animation-like state. 99 This might be instrumental in ameliorating suffering of patients after surgery, organs preservation and grafting, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from personal safety, H 2 S can also corrode metallic equipment, resulting in economic losses [6] , [7] . Besides, H 2 S not only is an indicator of food spoilage [8] , [9] , [10] , but also has emerged as a endogenous signal molecule with crucial pathophysiological roles in cardiovascular function [11] . Very recently, ppb-level trace H 2 S has also been used as a biomarker for the early diagnosis and therapy of lung diseases such like asthma [4] .…”
Section: Introductionmentioning
confidence: 99%